Normative video head impulse test data in subjects with and without vascular risk factors - Hansson, Anders; Salzer, Jonatan (European Archives of Oto-Rhino-Laryngology, 2020)
Abstract Purpose There is a paucity of age- and vascular risk factor-stratified video head impulse test (vHIT) vestibulo-ocular reflex (VOR) data in the literature. The aim of this study was to investigate the vHIT VOR properties in healthy subjects of different ages and subjects with vascular risk factors. Methods This was a prospective observational single-center study at a tertiary referral university hospital in northern Sweden. Healthy participants and subjects with vascular risk factors were investigated with a floor standing external camera vHIT device. Age-stratified mean VOR gain among healthy adults and between group gain and gain asymmetry differences were calculated. Results We included eighty-eight healthy adults with a mean (range) age of 50 (22–85) years and n = 48 stroke ward patients with vascular risk factors (but without vestibular disease) with a mean (range) age of 74 (42–92) years. The mean VOR gain of horizontal canals decreased at higher ages in healthy subjects ( r = − 0.32, p < 0.01, n = 167 canals). The age-stratified mean (SD) VOR gains were < 30 years: 0.98 (0.07), 30–39 years: 0.97 (0.07), 40–49 years: 0.98 (0.06), 50–59 years: 0.99 (0.06), 60–69 years: 0.93 (0.08), ≥ 70 years: 0.89 (0.15). No consistent differences between healthy subjects and subjects with vascular risk factors were seen except for a trend towards more pronounced gain asymmetries in the latter group. Conclusions Age, but not vascular risk factors influence VOR gain. Age-adjusted vHIT-measurements may be useful in acute vertigo stroke risk differentiation.